Convergence Rate of a Generalized Additive Schwarz Algorithm (Journal of Computational Mathematics, 2006)
The convergence rate of a generalized additive Schwarz algorithm for solving boundary value problems of elliptic partial differential equations is studied. A quantitative analysis of the convergence rate is given for the model Dirichlet problem. It will be shown that a greater acceleration of the algorithm can be obtained by choosing the parameter suitably. Some numerical tests are also presented in this paper.
Keywords: Schwarz additive algorithm; Convergence rate; Dirichlet problem.